Human Resource Management as a Psychological Energy Regulation System in Organizational Sustainability - Masruri, Masruri; Mahmudah, Siti (Jurnal Ragam Pengabdian, 2026)
Organizational dynamics in the digital era require a human resource management (HRM) approach that emphasizes the sustainable management of employees' psychological aspects. This study aims to analyze the role of HRM as a psychological energy regulation system in supporting organizational sustainability, focusing on medium-sized manufacturing companies in Greater Jakarta. Psychological energy, encompassing motivation, work engagement, and emotional resilience, is positioned as a strategic resource influencing organizational performance continuity. A quantitative explanatory design was employed, involving 72 employees from manufacturing companies. Data were collected through structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The variables include HRM practices, psychological energy regulation, and organizational sustainability. The findings indicate that HRM practices positively affect psychological energy regulation, which in turn enhances organizational sustainability, particularly in productivity and employee engagement. Psychological energy also mediates the relationship between HRM and organizational sustainability. This study contributes to HRM literature by positioning psychological energy as a key mechanism in maintaining organizational sustainability. Practically, the findings highlight the importance of developing HRM systems capable of managing employees' psychological capacity in facing complex organizational dynamics.